Association of Mitochondrial DNA Copy Number Variations with Triple-Negative Breast Cancer: A Potential Biomarker Study - Karin Manto; Sevdican Ustun Yilmaz; Zeliha Pala Kara; Halil Kara; Fatma Tokat; Cemaliye B. Akyerli; Cihan Uras; Meltem Muftuoglu; Ugur Özbek (Diseases)
Background/Objectives: Triple-negative breast cancer (TNBC) is a highly aggressive subtype with limited therapeutic options, and identifying reliable biomarkers for diagnosis and prognosis is crucial for improving patient outcomes. Mitochondrial DNA (mtDNA) copy number has been linked to an increased risk of developing various types of cancer, including breast cancer. However, there is a lack of understanding regarding how mtDNA copy number variations may influence the development and progression of TNBC. Methods: This study investigated mtDNA copy number in TNBC tumors and corresponding normal breast tissues from 23 TNBC patients who received neoadjuvant chemotherapy. The relative mtDNA copy number was estimated using quantitative PCR for the NADH dehydrogenase subunit 1 (ND1) and subunit 5 (ND5) regions. Results: The results showed a significant decrease in mtDNA copy number in TNBC tumor tissues compared to corresponding normal breast tissue. However, no significant correlation was found between mtDNA content and clinical parameters such as age, tumor size, or chemotherapy response. Conclusions: These results suggest that while mtDNA content decreases in TNBC tumors, it may not directly influence these clinical characteristics. Despite some inconsistencies in the literature regarding mtDNA dynamics in cancer, this study supports the potential of mtDNA as a biomarker for TNBC. Larger cohort studies are needed to further validate these results and explore the role of mtDNA in guiding personalized treatment strategies for TNBC patients.